Scaffold Proteins in Autoimmune Disorders - Joseph, Josna; Mathew, John; Alexander, Jessy (Current Rheumatology Reviews, 2024)
Cells transmit information to the external environment and within themselves through signaling molecules that modulate cellular activities. Aberrant cell signaling disturbs cellular homeostasis causing a number of different diseases, including autoimmunity. Scaffold proteins, as the name suggests, serve as the anchor for binding and stabilizing signaling proteins at a particular locale, allowing both intra and intercellular signal amplification and effective signal transmission. Scaffold proteins play a critical role in the functioning of tight junctions present at the intersection of two cells. In addition, they also participate in cleavage formation during cytokinesis, and in the organization of neural synapses, and modulate receptor management outcomes. In autoimmune settings such as lupus, scaffold proteins can lower the cell activation threshold resulting in uncontrolled signaling and hyperactivity. Scaffold proteins, through their binding domains, mediate protein- protein interaction and play numerous roles in cellular communication and homeostasis. This review presents an overview of scaffold proteins, their influence on the different signaling pathways, and their role in the pathogenesis of autoimmune and auto inflammatory diseases. Since these proteins participate in many roles and interact with several other signaling pathways, it is necessary to gain a thorough understanding of these proteins and their nuances to facilitate effective target identification and therapeutic design for the treatment of autoimmune disorders.
Keywords: proteins